From screen to space: evaluating Siemens’ Cinematic Reality application for medical imaging on the Apple Vision Pro - Luijten, Gijs; Faray de Paiva, Lisle; Krueger, Sebastian; Brost, Alexander; Mazilescu, Laura; Santos, Ana Sofia; Hoyer, Peter; Kleesiek, Jens; Schmitz, Sophia Marie-Therese; Neumann, Ulf Peter; Egger, Jan (Frontiers in Virtual Reality, 2026)
IntroductionAs one of the first research teams with full access to Siemens’ Cinematic Reality, we evaluated its usability and clinical potential for cinematic volume rendering on the Apple Vision Pro.MethodsWe visualized venous-phase liver computed tomography and magnetic resonance cholangiopancreatography scans from the CHAOS and MRCP_DLRecon public datasets, respectively. Fourteen medical experts assessed usability and anticipated clinical integration potential using standardized questionnaires (System Usability Scale and ISONORM 9242-110-S) and an open-ended survey. Our primary aim was not to validate direct clinical outcomes, but to evaluate the usability of Siemens’ Cinematic Reality on the Apple Vision Pro and gather expert feedback on potential use cases and missing features required for clinical adoption beyond educational purposes.ResultsTheir feedback identified feasibility, key usability strengths, and required features to catalyze the adaptation in real-world clinical workflows.ConclusionThe findings provide insights into the potential of immersive cinematic rendering in medical imaging and the needed features for clinical adoption as suggested by the medical experts. Siemens Cinematic Reality running on the Apple Vision Pro was deemed to have good usability, making it a promising tool.